2013
DOI: 10.2337/dc13-0842
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a Diet Low in Advanced Glycation End Products for 4 Weeks Improves Insulin Sensitivity in Overweight Women

Abstract: OBJECTIVE High-heat cooking of food induces the formation of advanced glycation end products (AGEs), which are thought to impair glucose metabolism in type 2 diabetic patients. High intake of fructose might additionally affect endogenous formation of AGEs. This parallel intervention study investigated whether the addition of fructose or cooking methods influencing the AGE content of food affect insulin sensitivity in overweight individuals. RESEARCH DESIGN AND METHODS Seventy-four overweight women were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 35 publications
6
98
1
Order By: Relevance
“…dietary random assignment, and the changes were temporally related to the changes in insulin sensitivity in participants as previously reported (17,22). We report that the changes in insulin sensitivity were likely due to changes in the dietary AGE content because diets were matched for both energy and macronutrient contents.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…dietary random assignment, and the changes were temporally related to the changes in insulin sensitivity in participants as previously reported (17,22). We report that the changes in insulin sensitivity were likely due to changes in the dietary AGE content because diets were matched for both energy and macronutrient contents.…”
Section: Discussionmentioning
confidence: 51%
“…Three trials have reported changes in the HOMA-IR in response to low-AGE dietary consumption in patients with type 2 diabetes (16) and in healthy, obese individuals without diabetes (17,18). The limitation of these studies was that they used the HOMA-IR, which is an indirect measure of insulin sensitivity and is unable to clearly differentiate the relative contribution of insulin sensitivity and secretion.…”
Section: Introductionmentioning
confidence: 99%
“…The AGE-RAGE axis is quite well established as a pathological pathway contributing to the complications of diabetes (6) and the metabolic changes leading to type 2 diabetes, including insulin resistance (7)(8)(9). More recent evidence suggests a role for AGEs and RAGE in the pathogenesis of type 1 diabetes (5,10,11).…”
mentioning
confidence: 99%
“…In addition, a positive but non-significant association was found between dietary AGEs and their corresponding protein bound plasma AGEs. These results are in line with previous studies 97,98,100,[111][112][113] , but the current study expands on these findings in several important ways. The presented study used state-of-the-art UPLC-MS/MS technique to analyze three different dietary AGEs and circulating AGEs.…”
Section: Dietarysupporting
confidence: 82%
“…Animal studies have shown that some of these dietary AGEs are absorbed and have pathological effects, such as inducing insulin resistance 92,95,96 . In humans, dietary AGE intervention studies have shown to increase circulating AGEs and markers of inflammation and endothelial dysfunction, and to impair flow-mediated dilation and insulin sensitivity [97][98][99][100][101] . Nevertheless, many studies on dietary…”
Section: Dietarymentioning
confidence: 99%